2019
DOI: 10.34297/ajbsr.2019.04.000840
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Nurses’ Compliance to Standard Precautions in Resource Scarce Settings

Abstract: This work is licensed under Creative Commons Attribution 4.0 License AJBSR.MS.ID.000840.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
2
9
0
1
Order By: Relevance
“…This was consistent with a study conducted by Clark, Jit, Warren-Gash, Guthrie, Wang, Mercer, Sanderson, McKee, Troeger, Ong 24 , they pointed out that most of nurses worried to be a vehicles to transmit the virus among their family members who already had a co-morbidity conditions, immunocompromised, or fragile to bear this virus. Also, the results of nursing staff shortage and work-pressure load are in agreement with other studies that reported lack of resources, workload, and lack of adherence with infection control policies as the main contributing factors of noncompliance of nurses with the SPs practices 2,22,25 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was consistent with a study conducted by Clark, Jit, Warren-Gash, Guthrie, Wang, Mercer, Sanderson, McKee, Troeger, Ong 24 , they pointed out that most of nurses worried to be a vehicles to transmit the virus among their family members who already had a co-morbidity conditions, immunocompromised, or fragile to bear this virus. Also, the results of nursing staff shortage and work-pressure load are in agreement with other studies that reported lack of resources, workload, and lack of adherence with infection control policies as the main contributing factors of noncompliance of nurses with the SPs practices 2,22,25 .…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, poor knowledge and compliance with SPs were revealed among many studies that could explain the high number of medical staff who were infected by COVID-19 among hospitalized patients 2,20 . In Jordan, little evidences available about the level of adherence of nurses about SPs practices and the main challenges that experience by them during their care of SARS-CoV-2 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the study from Eskander et al [26] rationalized noncompliance with SPs to limited staff numbers, increased workloads, and difficulty in maintaining hand hygiene. Zeb et al [19] documented the contributing factors towards non-compliance of nurses to SPs were limited facilities, high workloads due to staff shortages, and inefficient policies and regulations for infection prevention.…”
Section: Discussionmentioning
confidence: 99%
“…SPs require compliance by both doctors and nurses since they are partners in improving the quality of patient care. If either group does not comply with SPs, the standard of patient care in all areas of hospital settings can suffer [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Standard precautions pertain to the minimum standards of infection prevention practices that apply to patient care, regardless of confirmed or suspected infection status among patients in any setting where medical care is given (Centre for Disease Control and Prevention, 2018). According to Zeb et al (2019), these practice guidelines not only help to minimize the spread of infection among patients but also help to prevent healthcare workers from contracting infections when caring for patients. The five main domains in standard precautions include hand hygiene, use of Personal Protective Equipment (PPE), safe injection practices, safe handling and cleaning of b-37 contaminated equipment, and respiratory hygiene or cough etiquette (Labrague et al, 2012).…”
Section: Introductionmentioning
confidence: 99%